Optimalisasi Pemanfaatan Lahan Kehutanan dalam Rangka Peningkatan Kualitas Lingkungan dan Kesejahteraan Sosial Ekonomi Masyarakat Desa Sekitar Hutan: Studi Kasus di Kabupaten Sumedang - Rajati, Tati; Kusmana, Cecep; Darusman, Dudung; Saefuddin, Asep (Jurnal Manajemen Hutan Tropika, 2006)
To reserve forest land and improve people's income, Perum Perhutani Sumedang regency, together with the people surrounding the forest, makes a program to utilize the forest by using an agroforestry system. For that reason, the researcher is interested in doing research about the type of crops that can optimize forest land. The objective of the research is to analyze the utilization of forest land optimally and improve the social welfare of the people surrounding the forest in Cipadayungan, Sumedang. The result of the research indicates that the degree of erosion in the research field at the slopes of (0-<15)% and (15-<30)% is still under tolerated erosion, but the slope of .30% is beyond tolerated erosion. Types of crops that can be used to utilize the land without clearing grass growing on the forest floor are vanilla and coffee. Those plants are productive crops, while grass can protect the land against erosion.